Comparison of metabolic syndrome criteria in obese and overweight children - Astrid Anastasia Malonda; Helena Anneke Tangkilisan (Indonesian Pediatric Society, 2010)
Background Metabolic syndrome (MS) is a group of disorders which occur in relation to increasing body weight. Only a few studies have reported the differences in the fulfillment of MS criteria between obese and overweight children, and none were from Indonesia.Objective To detennine the differences in metabolic syndrome disorders between obese and overweight children.Methods A cross-sectional study was conducted in Manado from May to August 2010. The diagnosis of MS is established by fulfilling three of five criteria: waist circumference Â â‰¥90th percentile, blood pressure â‰¥ 90th Â percentile, fasting blood sugar (FBS) â‰¥ 100 mg/dL, triglycerides Â â‰¥110 mg/dL and high density lipoprotein (HDL) â‰¤40 mg/dL. Obesity was defined as body mass index (BMI) of> 3 SD and overweight as BMI of 2-3 SD. Results Results ere analyzed by x2 and t-test. Results Thirty obese and 30 overweight children aged 10-14years were examined for the disorders of MS. Twentyô€„three obese and 4 overweight children had waist circumferences Â â‰¥90th percentile. Seventeen obese and 3 overweight children had blood pressure Â â‰¥90th percentile. No significant differences in FBS, HDL, and triglycerides were observed between the two groups. Thirteen obese children met the MS inclusion criteria, while only 1 overweight child did so (P<0.001).Conclusions High blood pressure (â‰¥90th percentile) and waist circumference (â‰¥90th Â percentile) occurred were observed at higher frequency in obese children than in overweight children. The occurrence of MS in obese children was significantly higher than in overweight children.